What’s My Methodology? - Holmes, John (The ESPecialist, 2012)
This article addresses a major problem in the Brazilian ESP community, where members may define themselves as sharing a common methodology, but in practice sometimes depart from it. This leads to conflicts between what teachers recognise as an ‘official’ methodology and what really happens in the classroom. The article examines data to show the existence of the problem and searches for a solution in looking at different, and sometimes confusing uses of the term ‘methodology’ and their implications. In conclusion, the article proposes that methodology should be seen as a framework for making decisions as part of a dialogic process, and not as a fixed set of accepted practices.